Evidence of metabolic mechanisms playing a role in multiple insecticides resistance in Anopheles stephensi populations from Afghanistan - Safi, Noor Halim Zahid (Malar J, 2017)
BACKGROUND: Malaria is endemic in most parts of Afghanistan and insecticide-based vector control measures are central in controlling the disease. Insecticide resistance in the main malaria vector Anopheles stephensi from Afghanistan is increasing and attempts should be made to determine the underlying resistance mechanisms for its adequate management. METHODS: The contents of cytochrome P450s, esterases, glutathione S-transferases (GSTs) and acetylcholine esterase (AChE) activities were measured in the Kunar and Nangarhar populations of An. stephensi from Afghanistan and the results were compared with those of the susceptible Beech strain using the World Health Organization approved biochemical assay methods for adult mosquitoes. RESULTS: The cytochrome P450s enzyme ratios were 2.23- and 2.54-fold in the Kunar and Nangarhar populations compared with the susceptible Beech strain. The enzyme ratios for esterases with alpha-naphthyl acetate were 1.45 and 2.11 and with beta-naphthyl acetate were 1.62 and 1.85 in the Kunar and Nangarhar populations respectively compared with the susceptible Beech strain. Esterase ratios with para-nitrophenyl acetate (pNPA) were 1.61 and 1.75 in the Kunar and Nangarhar populations compared with the susceptible Beech strain. The GSTs enzyme ratios were 1.33 and 1.8 in the Kunar and Nangarhar populations compared with the susceptible Beech strain. The inhibition of AChE was 70.9 in the susceptible Beech strain, and 56.7 and 51.5 in the Kunar and Nangarhar populations. The differences between all values of the enzymes activities/contents and AChE inhibition rates in the Kunar and Nangarhar populations were statistically significant when compared with those of the susceptible Beech strain. CONCLUSIONS: Based on the results, the reported resistance to pyrethroid and organophosphate insecticides, and tolerance to bendiocarb in the Kunar and Nangarhar populations of An. stephensi from Afghanistan are likely to be caused by a range of metabolic mechanisms, including esterases, P450s and GSTs combined with target site insensitivity in AChE.